The effects of pre-task explicit instruction on the performance of a focused task. (February 2019) - Ellis, Rod; Li, Shaofeng; Zhu, Yan
Abstract: This study investigates the influence of pre-task explicit instruction on the performance of a focused task. 72 eighth-grade EFL learners were randomly assigned to two treatment conditions: Explicit Instruction + Task (EI) and Task-Only. Both groups performed two oral dictogloss tasks designed to provide opportunities for the production of past passive constructions. The EI Group received a brief grammar lesson on the English passive voice followed by 5 min of practice activities prior to task performance. The Task Only Group performed the same task but with no pre-task instruction or practice. The learners' task performance was coded on measures of complexity, accuracy, and fluency. The results showed that the pre-task instruction led to more frequent but not more accurate use of the target structure and that it had detrimental global effects on the complexity, accuracy and fluency of the learners' production. The results are considered in relation to a key issue in task-based instruction, namely whether or not to teach a grammatical structure prior to the performance of a focused task.